Upaya Pencegahan Penyebaran Covid-19 dan Usaha Mikro dan Kecil (UMK) Kelurahan Mambulau Kabupaten Kapuas Kalimantan Tengah - Aldy Juarnicko; Amalia Khairunnisa; Nadia Desyta Ramadani; Sugeng Mashabhi; Ahmad Mujaffar (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Thematic Real Work Lecture (KKN-T) is a form of implementation of an independent campus. Through this KKN-T activity, it seeks to improve the competence and role of students as agents of change in society, foster a spirit of volunteerism and be able to be responsible for the community. The implementation of KKN-T for the Mambulau village group was carried out in Mambulau Village, Kapuas Hilir District, Kapuas Regency, Central Kalimantan. The approach used in community service activities is participatory action research (PAR). The method of implementing KKN-T is carried out through posyandu and immunization activities, and counseling on the dangers of COVID-19 to the community. Supported by village officials and RT heads.  The work program "Efforts to Prevent the Spread of Covid-19 and Micro and Small Enterprises (UMK) in Mambulau Village" has been successfully implemented and smoothly. The people in the Mambulau sub-district were greatly helped by the activities to prevent the spread of COVID-19 carried out at the Posyandu. We also distributed paper bags containing masks and hand sanitizers, held socialization of nose washing at the Posyandu, then posted handwashing posters at places of worship, schools, sub-district offices, and health centers. People in the Mambulau village mostly plant banana trees around their home yards. So that a lot of post-harvest banana stem waste is found that is not utilized. Banana stem waste can be processed into chips. Banana stem chips have the potential to be used as a product for micro and small businesses that can improve the economy of the community in the Mambulau village.